Fiber quality at dehairing and characterization of skin follicle parameters in Peruvian Q’ara llamas - Machaca, Virgilio; Pinares, Rubén; Lozano, Franklin; Quispe-Quispe, Arturo; Machaca, Alex D.; Bustinza Choque, A. Víctor (Frontiers in Animal Science, 2025)
IntroductionAlthough Q’ara llama fleece was previously believed to lack quality attributes, the down fiber obtained during first shearing is of high quality. However, little is known about skin follicle parameters in Peruvian Q’ara llamas. In this context, the objective of this research was to compare fiber quality after manual dehairing and to characterize skin follicle parameters by body site, age, and sex.MethodsA total of 240 fiber samples were collected from the shoulders, mid-side, and rump of 80 Q’ara llamas, taking into account their age category and sex. Each unprocessed fiber sample was manually dehaired, yielding two subsamples of 240 each: down fibers and guard hairs. Only the unprocessed and down fibers were used for fiber measurements. According to IWTO-47 standards, an OFDA 2000 was used to measure mean fiber diameter, standard deviation, coefficient of variation, comfort factor, and fiber curvature. Skin biopsies were collected from 65 llamas under local anesthesia using an 8 mm punch to analyze follicle densities and the secondary-to-primary ratio. We performed Type I and the Tukey test (α = 0.05) on transformed data. Spearman’s correlation was applied without data transformation.Results and discussionManual dehairing improved textile fiber quality by reducing the diameter by 1.91 µm and the coefficient of variation by 3.05%. It also increased the comfort factor by 4.79% and fiber curvature by 3.49°/mm. Secondary follicle density (16.80 follicles per mm2) and secondary-to-primary follicle ratio (6.28) were similar across sex and body site. However, skin follicle density decreased in older llamas. There was a strong negative correlation (-0.82) between mean fiber diameter and comfort factor. Mean fiber diameter was negatively correlated with fiber curvature, total follicle density, and secondary to primary follicle ratio. However, comfort factor was positively correlated with fiber curvature, total follicle density, and secondary-to-primary follicle ratio. Total follicle density was positively associated with secondary-to-primary follicle ratio (0.52).ConclusionDehairing improves fiber quality. The main factor affecting fiber quality and skin follicles is age. Young Q’ara llamas have higher follicle density and produce down fiber with a diameter of 22.61 µm. However, body site and sex do not influence quality. The favorable relationship between fiber diameter and follicle density allows for the selection of high-quality fiber.